Hydro-powered Aquaponics Farming System - Yusvana, Rama (2014)
Universiti Malaysia Pahang – Faculty of Industrial Sciences and Technology showcased one of Green Technologies in Farming System at an event organized by Ministry of Energy, Green Technology and Water at the worldclass venue KLCC Convention Centre (16-19 October 2014). The participation of UMP at the event was also as part of ‘Knowledge Transfer Program’ 2014 – 2016, funded by the Ministry of Education in Malaysia, administered in UMP by the ‘Industry Partnership and Community Relation Division (BJIM)’. The event was attended by not less than 50,000 participants from 15 countries including Europe, US and Australia. With the theme of “Creating Green Wealth”, IGEM2014 aims to help pushing the rapid adoption of green technology to deliver impact for sustainable economic growth as well as to address environmental and food security issues. “Hydro-powered aquaponics farming system”, could save companies hundreds of thousand of dollars from paying annual utility cost and the associated tax on issues related to environmental carbon foot-print. The researcher however is in process of seeking protection of the intellectual property arising from this project and therefore unable to fully disclose some of the confidential information in this paper except some general and related information only.